Gonadal function in male mountain bikers - Yamaner, F.; Atmaca, H.; Bayraktaroglu, T.; Aydin, M.; Aydemir, S. (The Journal of Strength and Conditioning Research, 2011)
Some studies reported testicular disorders associated with biking in mountain cyclists, which include injuries, erectile dysfunction, and higher scrotal temperatures. But none of these studies evaluated gonadal function. Therefore, the aim of this study was to evaluate gonadal function in male mountain bikers. Twenty-two male professional mountain bikers and 30 healthy noncyclist controls were included in the study. The mean age and body mass index were similar in both groups. Fasting blood samples for the measurement of the levels of total testosterone (TT), sex-hormone binding globulin (SHBG), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) were obtained from all study participants before any physical activity. In addition, because insulin sensitivity and leptin modulate gonadal function, the concentrations of insulin, glucose, and leptin were also measured in the same samples. Calculated free testosterone (cFT) and bioavailable testosterone (bioT) were calculated from SHBG and TT. Basal hormonal levels including insulin, leptin, LH, FSH, SHBG, TT, glucose, and homeostasis model assessment scores were similar between the groups. However, bioT and cFT levels were significantly lower (p ? 0.05) in the mountain bikers than those in the controls. Despite the lower mean testosterone levels in the study group, the levels of LH and FSH were similar to controls. Insulin and leptin do not contribute to lower testosterone levels. In conclusion, male mountain bikers have lower testosterone concentrations compared to controls. This alteration cannot solely be explained by testicular dysfunction. The etiology of lower testosterone levels in cyclists appears to be complex and requires further research. The influence of such a decline on the athlete's performance, quality of life, and muscle strength is not known as yet.